Análise das subpopulações de células dendríticas no infiltrado subepitelial da doença enxerto contra hospedeiro crônica de mucosa bucal - Botari, Clara Marino Espricigo [UNESP] (2012)
The graft versus host disease (GVHD) or graft-versus-host-disease(GVHD) is a major cause of morbidity and mortality in patients who underwent hematopoietic stem cell transplantation (HSCT). It is a syndrome with various clinical, pathological and immunological. Aiming to contribute to clarifying the role of Myeloid dendritic cells, plasmacytoid cells and NK (natural killer) in chronic graft versus host disease (GVHD) and to clarify the mechanisms involved were examined microscopic sections of the oral mucosa of 26 patients with leukemia Acute Myeloid (AML) who underwent allogeneic hematopoietic stem cell in the Hospital Amaral Carvalho, Jau - SP, where 13 patients develop GVHDc oral mucosa and 13 did not develop GVHD. Microscopic sections were submitted to immunohistochemistry staining using monoclonal antibodies anti-CD1a, anti-CD56 and anti- CD123. The number of immunostained cells in the chorion (CD1a, CD123 and CD56) per square millimeter was calculated by dividing the mean of dendritic cells present in the 10 fields examined area covered by each specimen. The data were evaluated by Mann-Whitney. Results showed a statistically significant increase of myeloid dendritic cells CD1a (p = 0.02) and NK cells CD56 (p = 0.04) in patients with GVHDc compared with those without GVHDc. Analysis of CD123 immunostaining of no statistical difference between groups. It is concluded from this study that the development of chronic GVHD is participation of myeloid dendritic cells and NK cells in the chorion of oral mucosa